2018
DOI: 10.1002/cjoc.201800160
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Alkaloids from Indole‐3‐carbinol Exposed Culture of Daldiniaeschscholzii

Abstract: Two new and rare bioactive indoles named dalesindoloids A (1) and B (3), along with 3‐(1H‐indole‐3ylmethyl)‐2‐oxindole (2), were characterized from the indole‐3‐carbinol (I3C)‐exposed culture of Daldinia eschscholzii. The absolute configuration of 2 was determined by quantum chemical calculations of the electronic circular dichroism (ECD) spectrum. Dalesindoloids A and B were cytotoxic against the leukemia HL‐60 cell line with the IC50 values of 1.0 and 7.4 μmol/L, respectively, with the former being inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…This rationalization agrees with the oxygenation pattern of 1 and 2 and the monooxygenase-catalyzed 2,3-epoxidation of some indole motifs (a mimic of the polarized double bond of 4 , Fig. 3) in the fungal culture 46. The inter-cluster coupling gains reinforcements from the production of 1 and 2 via the heterologous co-expression of pksTL, ChrA and ChrB in A. oryzae , and through the co-culture of the two (co-)transformants, pksTL -AO and ChrA / ChrB -AO.…”
Section: Discussionsupporting
confidence: 87%
“…This rationalization agrees with the oxygenation pattern of 1 and 2 and the monooxygenase-catalyzed 2,3-epoxidation of some indole motifs (a mimic of the polarized double bond of 4 , Fig. 3) in the fungal culture 46. The inter-cluster coupling gains reinforcements from the production of 1 and 2 via the heterologous co-expression of pksTL, ChrA and ChrB in A. oryzae , and through the co-culture of the two (co-)transformants, pksTL -AO and ChrA / ChrB -AO.…”
Section: Discussionsupporting
confidence: 87%
“…Miscellaneous secondary metabolites from Hypoxylaceae (Fig. 14) From a mantis gut-derived D. eschscholtzii that also produced the dalescones, cultures supplemented with indole-3-carbinol yielded two (bis-)indole natural products named dalesindoloids A (81) to B [111]. Assessment of their cytotoxicity showed that 81 was strongly active against HL-60 cells (IC 50 1.0 µM), while being less active against several other cell lines.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…Li et al From the indole-3-carbinol exposed culture of D.eschscholzii, Lin et al [13] obtained two new alkaloids named dalesindoloids A (31) and B (32), shown in Figure 3. And then, this group [14] found two skeletally undescribed polyketide-indole hybrids from the indole-3-carbinol-exposed culture of D. eschscholzii named indolchromins A and B (33-34).…”
Section: Minireviewmentioning
confidence: 99%
“…[11] Dalesindoloid A (31) displayed moderate inhibition on the growth of S. aureus with its MIC value disclosed to be 9.1 μM, the MIC value of co-assayed streptomycin, 0.5 μM. [13] Daldispones B (56) showed moderate antimicrobial activity against Staphylococcus aureus, Enterococcus faecalis and Bacillus cereus with MIC of 32, 16, 32 μg/mL, respectively. [22] Helicascolide C (13), compound ( 15) and 8-hydroxylhelicascolide A (38), 6,8-dihydroxy-3-methyl-3,4dihydroisocoumarin (40) and compound (57) also showed mild antibacterial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation